Choice of generation volume models for electron beam induced current computation - Ong, Vincent K. S. (2010)
The spatial distribution of the electron-hole pairs generated by the electron beam is commonly called the generation volume or interaction volume. The generation volume affects the electron beam-induced current (EBIC) profile. This effect of the generation volume on the EBIC profile is particularly true for regions near to the semiconductor junctions. Mathematical models have been proposed for use in the computation of EBIC profiles. Three pear-shaped generation volume distributions were analyzed by comparing the resulting EBIC profiles to the profile obtained from the data using theMonte Carlo simulations. The result shows that the Bonard model gives an EBIC profile that is closest to the one computed using the Monte Carlo simulation. This result is easily observed in the first and the second derivatives of the semilogarithmic EBIC profiles.